Butyrate and Class I Histone Deacetylase Inhibitors Promote Differentiation of Neonatal Porcine Islet Cells into Beta Cells - Yichen Zhang; Yutian Lei; Mohsen Honarpisheh; Elisabeth Kemter; Eckhard Wolf; Jochen Seissler (Cells, 2021)
Neonatal porcine islets-like clusters (NPICCs) are a promising source for cell therapy of type 1 diabetes. Freshly isolated NPICCs are composed of progenitor cells and endocrine cells, which undergo a maturation process lasting several weeks until the normal beta cell function has developed. Here, we investigated the effects of short-chain fatty acids on the maturation of islet cells isolated from two to three day-old piglets. NPICCs were cultivated with acetate, butyrate and propionate (0–2000 µM) for one to eight days. Incubation with butyrate resulted in a significant upregulation of insulin gene expression and an increased beta cell number, whereas acetate or propionate had only marginal effects. Treatment with specific inhibitors of G-protein-coupled receptor GPR41 (β-hydroxybutyrate) and/or GPR43 (GPLG0974) did not abolish butyrate induced insulin expression. However, incubation of NPICCs with class I histone deacetylase inhibitors (HDACi) mocetinostat and MS275, but not selective class II HDACi (TMP269, MC1568) mimicked the butyrate effect on beta cell differentiation. Our study revealed that butyrate treatment has the capacity to increase the number of beta cells, which may be predominantly mediated through its HDAC inhibitory activity. Butyrate and specific class I HDAC inhibitors may represent beneficial supplements to promote differentiation of neonatal porcine islet cells towards beta cells for cell replacement therapies.